Vitimização percebida e vivenciada por trabalhadores da saúde: Violência no ambiente de trabalho e das relações sociais - Casaes, Fabiana Mandelo (2017)
Objective: To identify factors associated with violence witnessed and experienced by health workers in Bahia municipalities. Method: This is an exploratory cross-sectional study, which is part of the multicentric research "Working conditions, conditions of employment and health of health workers in Bahia", carried out in the Basic Attention and Medium Complexity services in the Sanitary District of Historic Center of Salvador and in the municipalities of Feira de Santana, Santo Antônio de Jesus, Jequié and Itabuna, in the years 2011 and 2012. The population of the study was constituted by 6,191 workers. In this study, the dependent variable was the violence experienced by the worker outside the workplace and the violence witnessed by health workers in their workplace. The analysis was made through Hierarchical Logistic Regression based on the conceptual hierarchical model for violence outside work and the multivariate analysis with Poisson Regression for violence witnessed in the workplace. Results: The analysis showed a positive association between age, marital status, schooling, professional category and respiratory diseases for the violence experienced by health workers outside work. The violence witnessed by health workers remains statistically associated with high school / technical education, higher education, post-graduation, threatened personal security, Cap X, health unit. Final Considerations: It has been found that in all contexts, a prevalence of violence is an important fact and that it is an observatory with caution, both on the part of the workers, with the management of public powers. The factors that contributed the most to the dissemination of problems, both in the national and international literature, and ratify the importance of this work. This study was developed with the health team because of the importance of its native role in the entire population, but it is worth mentioning an eminence of future work on the problem, which is that you know the expansion of study places, expanding to other states And Municipalities, in order to compare the reality in which health workers live, as a study population, is already an issue that involves all members of society without distinction.